Differential Gene Expression in Exfoliation Syndrome and Exfoliation Glaucoma in the Conjunctiva of Black South Africans - Hulley, Michaella Robyn (University of the Witwatersrand, Johannesburg, 2024)
Glaucoma is a heterogeneous group of clinically and genetically complex optic neuropathies. The most prevalent identifiable secondary cause of glaucoma is the ocular manifestation of exfoliation syndrome (XFS), known as exfoliation glaucoma (XFG), a severe form of glaucoma characterized by rapid progression. While XFS is systemic, XFG is defined by fibrillar extracellular matrix (ECM) deposits in the eye. XFG has a recognised genetic aetiology, specifically with contributions from LOXL1 variants, however the molecular pathogenesis remains unclear. Conjunctival cells have not previously been used for whole transcriptome sequencing, and gene expression studies on XFG are lacking, particularly in South Africa. The aim of this study was to validate the use of conjunctival cells for whole transcriptome sequencing and interrogate the gene expression profiles of individuals with XFS and XFG. Conjunctival cells were collected from 19 cases and 15 control participants for RNA extraction, cDNA library construction and sequencing. Differential gene expression was assessed between cells from cases and controls and 81 genes were found to be differentially expressed, with 80 upregulated in cases. Interestingly, LOXL1, which has shown contradictory expression results in previous studies, was not identified as differentially expressed. The most significant overexpression was of the CCN2 gene, which encodes a matricellular protein that interacts with structural ECM molecules. A potential novel pathway involving megakaryocytes and the activation of neutrophils was, however, identified. Megakaryocytes and neutrophils are both involved with interstitial fibrosis, with neutrophils also responding to chemotactic signals to induce inflammation. The inflammatory pathway has long been associated with XFS, XFG and other fibrotic disorders, such as Alzheimer's disease and rheumatoid arthritis. Genes involved in the inflammatory process were overexpressed in XFG, including TGF-β, IL-1β, IL- 33, EGR1 and EGR3. EGR1 and EGR3 are regulated by fibrotic signals and therefore play an important role in fibrosis, which may contribute to XFS fibrillar deposits. They are also regulated by TGF-β, thus supporting a complex interplay of the inflammatory process and fibrosis in XFS pathogenesis
A Thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy. to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: Exfoliation glaucoma; Exfoliation syndrome; Transcriptomics; Gene expression; UCTD; SDG-3: Good health and well-being